PENGARUH PERSONAL BACKGROUND DAN PENGETAHUAN AUDITOR INSPEKTORAT TENTANG ANGGARAN TERHADAP PENGAWASAN KEUANGAN DAERAH (STUDI PADA INSPEKTORAT KOTA LHOKSEUMAWE) - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2018)
This research was intended to know The Influence Of Personal Background And Auditor Budget Knowledge For Region Financial Control. The independent variable in this study is personal background and Auditor Budget Knowledge. Dependent variable in this study is Region Financial Control. This study used a sample of auditor in the Inspektorat Lhokseumawe. Data were collected using total sampling, and tested using descriptive statistical analysis, test data quality, classic assumption test, multiple regression analysis, F test, test the coefficient of determination and t test (partial). The test results show personal background (gender, age, and the long time work) with partial test show no effect on the region financial control, and personal background (graduate and spesific graduate) show is positive effect on the region financial control. The test results with the auditor knowledge about budgets is positive effect on the region financial control. The results with the simultan test show is personal background and the auditor knowledge about budgets is positive effect on the region financial control.